2015
DOI: 10.2987/moco-31-03-223-232.1
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Suna Trap for Improved Survival and Quality of Mosquitoes in Support of Epidemiological Studies

Abstract: Monitoring adult mosquito populations provides information that is critical for assessing risk of vector-borne disease transmission. The recently developed Suna trap was found to be a very effective trap when baited with an attractive odor blend. A modification of this trap was tested to improve its function as a tool for monitoring mosquito populations, including Anopheles coluzzii (An. gambiae sensu stricto molecular form M), Aedes aegypti, and Culex pipiens. The modified Suna trap (Suna-M) was altered by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The laboratory data were analysed by using a generalized linear model (GLM, binomial, logit link function and dispersion estimated) to test for differences in ratio of mosquitoes caught and trap entry response rates of the mosquitoes towards CO 2 and odour blends, and different trap types [32]. The ratio was calculated as the number of mosquitoes caught in the treatment trap divided by the total number of mosquitoes caught in both traps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The laboratory data were analysed by using a generalized linear model (GLM, binomial, logit link function and dispersion estimated) to test for differences in ratio of mosquitoes caught and trap entry response rates of the mosquitoes towards CO 2 and odour blends, and different trap types [32]. The ratio was calculated as the number of mosquitoes caught in the treatment trap divided by the total number of mosquitoes caught in both traps.…”
Section: Discussionmentioning
confidence: 99%
“…Cage experiment 1: attractiveness of the BG-Suna trap in normal and inverted position. A previous study performed by Verhulst et al [32] showed that Ae. aegypti can be attracted to a BG-Suna trap when baited with the MB5 blend and CO 2 .…”
Section: Experimental Designmentioning
confidence: 93%
See 1 more Smart Citation
“…Whether the chemical release rates and hence performance of the MB5-baited Suna trap might also be affected by night-time temperatures during trapping needs further investigations. Mechanisms to increase the released concentrations and improve the dispersion might be explored in future by modifying the Suna traps (103) or surveying alternative traps and baits (29,78,(104)(105)(106). A recent study for example suggested the combination of trans uthrin treated fabric on eave gaps with BG Malaria traps (Biogents, Germany) and suggested a larger distance of the pull trap from the human host, nevertheless the authors also found only a very marginal addition of protection from the traps in preventing An.…”
Section: Discussionmentioning
confidence: 99%
“…For the dual choice experiments, a GLM with a binomial distribution, logit link function and estimated dispersion [35] was used. The response variable of the GLM was the capture percentage, defined as the ratio between number of captures by one trap and the number of captures by both traps.…”
Section: Discussionmentioning
confidence: 99%